2021
DOI: 10.1111/jgs.17220
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hurricane Irma on daily direct‐care nurse staffing in nursing homes

Abstract: Objectives To examine the effect of Hurricane Irma on staff‐related financial expenditures and daily direct‐care nurse staffing levels. Design Retrospective cohort study. Setting September 3–24, 2017 in the state of Florida, United States. Hurricane Irma made landfall on September 10, 2017. Participants Six hundred and fifty‐three nursing homes (NHs), 81 evacuated facilities, and 572 facilities that sheltered‐in‐place. Measurements This study used data from Payroll‐Based Journaling (PBJ), Certification and Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Prior work from Hurricane Irma in September 2017 suggests that NHs increase all types of direct‐care nurse staffing in preparation for major hurricanes, but that evacuating a facility requires an even greater staffing response 68 . Unfortunately, lower‐quality NHs increased their staffing levels the least and opted to retain fewer RNs compared to higher‐quality NHs during Hurricane Irma 69 . Because direct‐care staff implements the 4Ms (i.e., resident goal planning and fulfilling preferences/wishes, providing medications and identifying adverse drug‐related events, recognizing and managing cognitive and mental health disorders, assisting with transfer and mobility), it is crucial for NHs to maintain adequate staffing levels to meet the needs of residents during disasters.…”
Section: The Age‐friendly 4m Frameworkmentioning
confidence: 99%
“…Prior work from Hurricane Irma in September 2017 suggests that NHs increase all types of direct‐care nurse staffing in preparation for major hurricanes, but that evacuating a facility requires an even greater staffing response 68 . Unfortunately, lower‐quality NHs increased their staffing levels the least and opted to retain fewer RNs compared to higher‐quality NHs during Hurricane Irma 69 . Because direct‐care staff implements the 4Ms (i.e., resident goal planning and fulfilling preferences/wishes, providing medications and identifying adverse drug‐related events, recognizing and managing cognitive and mental health disorders, assisting with transfer and mobility), it is crucial for NHs to maintain adequate staffing levels to meet the needs of residents during disasters.…”
Section: The Age‐friendly 4m Frameworkmentioning
confidence: 99%
“…Disasters increase staffing needs and costs, as suggested in a study of a one-time state of Florida effort to reimburse NHs for 2004–2005 hurricane expenses ( Thomas et al, 2010 ). Recent research found that Hurricane Irma also increased NH staffing costs, particularly for NHs that evacuated, suggesting the need for a renewed effort to help facilities pay for needed disaster staffing ( Jester et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…After crossing the Florida Keys, it made landfall in southwest Florida as a Category 3 storm with a wind field that threatened the entire state as it travelled north ( Cangialosi et al, 2018 ). Among those at risk at the time were an estimated 71,000 residents of Florida’s 670 NHs and 85,000 residents of the 3,112 ALCs ( Jester et al, 2021 ; Peterson et al, 2020 ). In the present study, we conducted qualitative interviews and focus groups with owners and administrators of NHs and ALCs in Florida concerning their experiences related to Hurricane Irma, including actions they took to prepare for the hurricane and challenges they faced during and after the storm.…”
mentioning
confidence: 99%
“…6,7 The adverse outcomes incurred by nursing home residents following Hurricanes Katrina and Rita highlight this population's unique susceptibility to environmental exposures and the importance of adequate emergency preparedness. 8,9 Despite the risks borne by nursing home residents, variation in their exposure to potential environmental hazards is not well characterized. It is also uncertain whether nursing homes at increased risk of exposure are adequately prepared to safeguard residents upon encountering environmental hazards.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,16 These preventable deficiencies heighten the risk of resident morbidity and mortality following exposure to severe weather events. [6][7][8]17 In this study, we estimate the prevalence of nursing homes that are subject to severe hurricanerelated inundation within Coastal Atlantic and Gulf Coast states. We then evaluate whether exposure status is associated with adherence to emergency preparedness standards by nursing homes across regulatory regions overseen by 5 CMS regional offices.…”
Section: Introductionmentioning
confidence: 99%